The Role of Financial Inclusion: Development MSMEs Financial Management of Cirebon in Indonesia - Setiana, Cisa; Hardyanti, Tia; Mardiyani (Dinasti Publisher, 2025)
Analyzing the influence of fintech and understanding financial literacy on MSME financial management in Cirebon City consider financial inclusion as a mediating factor in this relationship. This research uses quantitative methods and the type of research used was associative causal with a population of all MSMEs in Cirebon City. The sample obtained was 150 respondents using the SEM PLS PLS 4 method for analyzing causal relationships between variables. Findings: The findings in this research emphasize the importance of increasing financial literacy and access to financial inclusion for MSME players, as well as the need for more effective training programs in the use of fintech to improve financial management. Increasing understanding and use of financial technology is expected to support the sustainability and growth of MSMEs in Cirebon City. The findings offer understanding and use of financial technology, it is hoped that it can support the sustainability and growth of MSMEs in Cirebon City. However, there are limitations in this research which can be taken into consideration for further research so that the results obtained are maximized, by not just limiting it to city areas. Apart from that, support from previous research for the results of testing the same hypothesis is still relatively small. This research addresses the gap in understanding the impact of fintech on SMEs and offers new insights into financial literacy in managing their finances.